The Effectiveness of Using SCAMPER Model for Teaching English Language in Developing Creative Expression Skills among Basic Stage Students - Alqtishat, Tayseer Abdullah Ali; Al-Hasba, Nora Salem (Journal of Educational and Psychological Sciences, 2021)
The current study sought to identify the effectiveness of using the SCAMPER model to teach English in developing the skills of creative expression among elementary school students, and the study sample consisted of (67) students from the tenth grade of basic school from Al-Qadisiyah Secondary School for Boys affiliated to the Education Directorate of Basira District in Tafila Governorate During the first semester of the academic year 2019/2020, a department was appointed that included (32) students as an experimental group, and another consisting of (35) students as a control group in the random way, and to achieve the objectives of the study, the researcher designed two tests of creative expression skills and creative conversation skills. In addition, a guide was designed to use the scamper model in teaching the first unit "Starting Out" of the tenth grade English language book "Action Pack 10", and the validity and reliability of the study tools were verified. In addition, the first unit "Starting Out" was taught using the SCAMPER model for the experimental group, while the control group studied the same unit in the usual way, and the study concluded that there were statistically significant differences at the level (α ≤ 0.05) in the performance of the tenth-grade students of the basic writing tests. Creative and creative speaking in the English language after the method variable (teaching using the scamper model), and the study recommended the use of the scamper model in teaching English language skills to all grades as well as giving educational supervisors training courses for English language teachers on employing the SCAMPER model in teaching English language research.
Keywords: Scamper Model; Creative Expression Skills; English Language Teaching; basic stage students